Feasibility of peripheral OCT imaging using a novel integrated SLO ultra-widefield imaging swept-source OCT device. - Sodhi, Simrat K; Golding, John; Trimboli, Carmelina; Choudhry, Netan (Springer Science and Business Media LLC, 2021)
PURPOSE: To describe the feasibility of peripheral OCT imaging in retinal diseases using a novel full-field device. METHODS: A total of 134 consecutive eyes were referred and imaged on the Optos Silverstone swept-source OCT (SS-OCT) (Optos PLC; Dunfermline, UK). Scanning laser ophthalmoscope (SLO) images and the associated SS-OCT images were obtained in the posterior pole, mid-periphery or far periphery based on the nature of the referral and on new areas of interest observed in the optomap images at the time of imaging. RESULTS: A total of 134 eyes (96 patients) were enrolled in the study. One hundred and twenty-five eyes (91 patients) with 38 retinal pathologies were prospectively assessed and 9 eyes (5 patients) were excluded due to incomplete image acquisition. The average age of the subjects was 54 years (range 21-92 years). Thirty-nine out of 125 eyes (31%) had macular pathologies. Eighty-six out of 125 eyes (69%) had peripheral only pathologies, an area which cannot be visualized by standard OCT devices with a 50 degree field-of-view. CONCLUSIONS: The ability to capture peripheral pathologies using an integrated SLO-UWF imaging with full-field swept-source provided high-grade anatomical insight that confirmed the medical and surgical management in a majority of cases. Its use in the mid- and far periphery provides a holistic clinical picture, which can potentially aid in the understanding of various retinal pathologies.
Keywords: Far periphery; Full-field; Mid-periphery; Optical coherence tomography; Peripheral; Swept-source OCT; Adult; Aged; Aged, 80 and over; Feasibility Studies; Fluorescein Angiography; Humans; Middle Aged; Ophthalmoscopes; Retina; Tomography, Optical Coherence; Young Adult